Effet de la substitution de la présure par la pepsine de poulet dans la coagulation des laits destinés à la transformation fromagère - BOURAHLA, BOUCHRA HALIMA (My University, 2020)
In This study we tried to substitute commercial rennet with chicken pepsin as the milk coagulant. To achieve this objective, we proceeded to the extraction of chicken pepsin from proventricules, and the characterization of the enzymatic extract obtained. In order to compare the effect of pepsin to that of rennet, we approached the technological clotting times represented by flocculation and setting, the proteolytic activity was controlled by the kinetics of coagulation. The results obtained showed the conformity of the flocculation times respecting the IDF standard between 8 and 15 minutes. Coagulation with chicken pepsin occurs at a rate of release of non-protein nitrogen identical to that of commercial rennet. Using controlled dilutions of enzymatic extracts, pepsin gel exhibited the same rheological behavior as renesure gel with floculation between 12 and 14.5 minutes and an average U.A.C. between 0.12 and 0.15 unit/ml. No significant difference was observed which could prevent the substitution of rennet by chicken pepsin during the enzymatic coagulation phase.
Keywords: coagulation; chicken pepsin; rennet; proteolysis.